Differences in On-the-Job Learning across Firms - Jaime Arellano-Bover; Fernando Saltiel (Center for Economic Studies and ifo Institute (CESifo), 2024)
We present evidence that is consistent with large disparities across firms in their on-the-job learning opportunities, using administrative datasets from Brazil and Italy. We categorize firms into discrete "classes"—which our conceptual framework interprets as skill-learning classes—using a clustering methodology that groups together firms with similar distributions of unexplained wage growth. Mincerian returns to experience vary widely across experiences acquired in different firm classes. Four tests leveraging firm stayers and movers, occupation and industry switchers, hiring wages, and displaced workers point towards a portable and general human capital interpretation. Heterogeneous employment experiences explain an important share of wage variance by age 35, thus contributing to shape wage inequality. Firms' observable attributes only mildly predict on-the-job learning opportunities.
Keywords: J24; J31; 330; human capital; firms; on-the-job learning; wage growth